2017
DOI: 10.1016/j.celrep.2017.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Intrinsic Axon Growth Modulators for Intact CNS Neurons after Injury

Abstract: SUMMARY Functional deficits persist after spinal cord injury (SCI) because axons in the adult mammalian central nervous system (CNS) fail to regenerate. However, modest levels of spontaneous functional recovery are typically observed after trauma and are thought to be mediated by the plasticity of intact circuitry. The mechanisms underlying intact circuit plasticity are not delineated. Here, we characterize the in vivo transcriptome of sprouting intact neurons from Ngr1 null mice after partial SCI. We identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 46 publications
10
94
0
Order By: Relevance
“…This study avoided any issues related to tissue culture prior to expression analysis, but the overlap with functional axon regeneration genes remained minimal with 5 genes in total, and was non-significant (Figure S2A). The functional regeneration genes were identified here in cortical neurons, so we also assessed overlap with our RNA-seq expression profile of sprouting corticospinal neurons after pyramidotomy (Fink et al, 2017). This expression survey also revealed minimal and statistically insignificant overlap with functional effects on axon regeneration, though the absolute numbers were higher than for the DRG studies (Figure S2B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study avoided any issues related to tissue culture prior to expression analysis, but the overlap with functional axon regeneration genes remained minimal with 5 genes in total, and was non-significant (Figure S2A). The functional regeneration genes were identified here in cortical neurons, so we also assessed overlap with our RNA-seq expression profile of sprouting corticospinal neurons after pyramidotomy (Fink et al, 2017). This expression survey also revealed minimal and statistically insignificant overlap with functional effects on axon regeneration, though the absolute numbers were higher than for the DRG studies (Figure S2B).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the most common approach to identifying genes involved in regeneration has focused on expression surveys, most commonly at the mRNA level (Belin et al, 2015; Bonilla et al, 2002; Chandran et al, 2016; Fink et al, 2017; Tanabe et al, 2003; Tedeschi et al, 2016). Such previous work has the premise that genes involved in regulating regeneration are controlled transcriptionally by injury.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses revealed that components of the lysophosphatidic acid (LPA) pathway were differentially expressed, with a substantial suppression of LPA receptor 1 (Lpar1) in actively sprouting neurons. Administration of AM095, a small molecule inhibitor of Lpar1, improved CST sprouting and motor behaviors in mice that had undergone unilateral pyramidotomy (Fink et al, ). These exciting results pave the way for further exploration of new targets and pharmacological agents to enhance axonal sprouting and functional recovery.…”
Section: Sprouting From Spared Axonsmentioning
confidence: 99%
“…Neuroligins interact with neurexins, a family of presynaptic adhesion molecules, and are major regulators of synapse development and function 30 . Interestingly, Inpp5k has been reported to act as a lysophosphatidic acid signaling modulator, and its overexpression promotes the intrinsic axon growth of corticospinal axons 31 . Considering these reports and the results of our NGS analysis, it is presumed that neurons cultured on the microgrooved nanosheet become more mature than neurons cultured on the flat nanosheet.…”
Section: Differentially Expressed Gene Analysis In Neuronal Cells Culmentioning
confidence: 99%